(untitled) (Academia Science Repository, 2023)
In order to create the most favorable investment environment for attracting direct investments in the Republic of Uzbekistan, liberalize the economy, reform public administration, limit interference in the activities of business entities, reduce licensing and permitting procedures, and wide-scale measures have been taken to simplify, provide free access to goods (works and services), as well as create the necessary infrastructure in the regions. Develop ways to increase the role of the capital market in creating a favorable investment environment in our country main directions set, in our republic work on ways to increase the role of the capital market in creating a favorable investment environment work on the way out and can be used in scientific research devoted to statistical analysis.